Estructura electrónica en aleación de AlP calculada con el método LMTO - Cabrera, Cesar (2018)
The electronic structure and the total energy of the crystalline alloy Aluminun-Phosphide (AlP) is studied using a local type LDA potential. Energy bands and the density of two States are calculated by solving the Kohn-Sham equation for the crystalline solid with the LMTO method. The electronic structure with a band of forbidden energy of 2.56 eV for energy total minimum of -19.138 Ry ts experimental results.